2012
DOI: 10.1165/rcmb.2012-0095oc
|View full text |Cite
|
Sign up to set email alerts
|

CD11c+/CD11b+ Cells Are Critical for Organic Dust–Elicited Murine Lung Inflammation

Abstract: Organic dust exposure in the agricultural industry results in significant lung disease. Macrophage infiltrates are increased in the lungs after organic dust exposures, yet the phenotype and functional importance of these cells remain unclear. Using an established intranasal inhalation murine model of dust-induced lung inflammation, animals were treated once or daily for 3 weeks with swine confinement organic dust extract (DE). Repetitive DE treatment for 3 weeks resulted in significant increases in CD11c(+)/CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 54 publications
4
43
0
Order By: Relevance
“…Animals exposed to OD display severe neutrophilia (34), and when the kinetics have been studied, previous studies have shown that repeated OD exposure in mice results in a marked increase in pulmonary neutrophil populations that peak 24 h following OD exposure (33). Due to the efficacy of 100 g of OD in inducing AHR as well as increased macrophage and neutrophil numbers in BAL in the present study, this dose was well-suited for all subsequent experiments, as both macrophages and neutrophils have been shown to be important in mediating the OD response (32).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Animals exposed to OD display severe neutrophilia (34), and when the kinetics have been studied, previous studies have shown that repeated OD exposure in mice results in a marked increase in pulmonary neutrophil populations that peak 24 h following OD exposure (33). Due to the efficacy of 100 g of OD in inducing AHR as well as increased macrophage and neutrophil numbers in BAL in the present study, this dose was well-suited for all subsequent experiments, as both macrophages and neutrophils have been shown to be important in mediating the OD response (32).…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, OD exposure induces pulmonary inflammation in humans typified by an increase in neutrophils and macrophages in BAL fluid (19,29,32). Animals exposed to OD display severe neutrophilia (34), and when the kinetics have been studied, previous studies have shown that repeated OD exposure in mice results in a marked increase in pulmonary neutrophil populations that peak 24 h following OD exposure (33).…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous ODE was collected and prepared as previously described (14), and as described in the online supplement. To broaden the applicability of systemic ODE-induced lung injury bone consequences, comparison experiments were performed with LPS (100 ng per 30 ml, which is approximately double the concentration of detectable LPS in 12.5% ODE, from Escherichia coli O55:B5; Sigma Chemical Co., St. Louis, MO) and Staphylococcus aureus PGN (100 mg per 30 ml; Sigma Chemical Co.), which also remains consistent with our previous work comparing ODE-induced responses to PGN (6).…”
Section: Bioaerosol Agentsmentioning
confidence: 99%
“…The organic dust exposure is complex, involving a wide diversity of microbial motifs (e.g., peptidoglycans [PGNs] and endotoxin) and particulate matter, which elicit airway inflammatory responses in mice (7,13). Namely, repetitive organic dust exposures induce the development of lymphoid aggregates and peribronchiolar/ vascular inflammation, comprised of T and B lymphocytes and macrophages with associated neutrophil recruitment (5,14,15). Although LPS remains an important component, the inflammatory lung response is not entirely dependent on LPS (6,16), and moreover, Gram-positive components, including PGN (7,13,17), appear to be the major factors driving lung consequences.…”
mentioning
confidence: 99%
“…In recent studies, several groups of investigators suggested that these two populations of lung macrophages play opposing roles in lung injury. Alveolar macrophages appear to limit neutrophil influx into the lung during acute lung injury (9) or chronic exposure to organic dust (10), whereas interstitial macrophages promote neutrophil extravasation (11,12). An additional layer of complexity is added by the phenotypic plasticity of macrophages.…”
mentioning
confidence: 99%